Factors Influencing the Incidence of Bribery Payouts by Firms: A Cross-Country Analysis - Chen, Yanjing (Journal of business ethics, 2008)
This article explores micro- and macro-level variables that influence the incidence of bribery payouts by firms. A rich data set with information from 55 countries was utilized to achieve this objective. Results of logit regression models indicate that there are a number of micro- and macro-level factors that significantly affect the incidence of bribery payouts. This suggests that it is not only the characteristics of a firm but also the environment of doing business that affect the firm’s bribery decision. The results of this study provides information that may help firms develop strategies to reduce corruption in their respective industries and thereby improve their image of corporate social responsibility. The analysis also points to possible policy directions that governments could undertake in order to reduce the incidence of bribery in their country.